The mitochondrial complex II and ATP-sensitive potassium channel interaction: Quantitation of the channel in heart mitochondria - Wojtovich, Andrew P. (2010)
The mitochondrial ATP-sensitive potassium channel (mK(ATP)) is important in cardioprotection, although the channel remains molecularly undefined. Several studies have demonstrated that mitochondrial complex II inhibitors activate the mK(ATP), suggesting a potential role for complex II in channel composition or regulation. However, these inhibitors activate mK(ATP) at concentrations which do not affect bulk complex II activity. Using the potent complex II inhibitor Atpenin A5, this relationship was investigated using tight-binding inhibitor theory, to demonstrate that only 0.4% of total complex II molecules are necessary to activate the mK(ATP). These results estimate the mK(ATP) content at 15 channels per mitochondrion.